ANALISIS EXPERIENTIAL MARKETING DALAM STASIUN RADIO BERFORMAT OLAHRAGA (STUDI PADA PROGRAM OFF AIR NONTON BARENG RADIO 96.4 BOBOTOH FM BANDUNG): Rochmat Fauzi, Faridhian Anshari - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Radio is one part of the mass media that can reach a large audience. One of them is the radio with a sports format. The format determines how radio programs are planned and implemented, one of which is the program off air radio. Marketing important to applied in order to achieve profitability, and create a consumer experience to the company through the program off air that event. One of them is with experiential marketing through strategic experience models (SEMs). In SEMs there are five elements to create an experience in the minds of consumers and marketing tool called experience provider (EXPROS). This research aims to determine the planning and SEMs elements in the program off air “nonton bareng” by 96.4 Bobotoh FM Bandung Radio. This research use a qualitative approach and descriptive research. The data validity of research by triangulation. The results in this research is unsuccesfull event planning program off air “nonton bareng” according to the characteristics, positioning and radio format. Expereintial marketing planning is not fully planned.The fifth element of strategic experience models contained in the “nonton bareng” is sense element utilizing the senses of sight, the emotional element with a positive feel, think elements with creative thinking, the elements act with spontaneity and invitations, and elements relate to relationships with employees and the